Comparison of continuous and stop-and-go scanning techniques in photoacoustic tomography - Sharma, Arunima (2018)
Photoacoustic tomography is an emerging imaging modality which has paved its way in preclinical and clinical trials owing to the multiple advantages it offers. A typical PAT system consists of a laser beam which homogeneously illuminates the sample giving rise to photoacoustic (PA) waves, which are collected using an ultrasound transducer (UST) rotating around the sample. Low cost, high sensitivity and easy availability have made single-element transducers (SETs) a preferred choice for acquiring these A-lines PA signal. Two methods have been reported for collection of these A-lines by SETs- (1) Stop-and-go scan and (2) Continuous scan. In stop-and-go scan, the stepper motor moves the SET to a predefined position where the SET collects multiple A-lines. Once the desired number of A-lines at that point have been collected and saved, the stepper motor moves to the next position and the process continues. A continuous scan is one in which the stepper motor rotates the SET continuously at a predefined speed. The A-lines are thus collected by a moving SET and are saved once the motor has stopped. In this work, we have compared the two types of scanning methods in terms of image quality, signal-to-noise ratio and time of scan by performing experiments on phantoms.